2017
DOI: 10.4103/ijccm.ijccm_105_17
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide as an alternative to insulin for glycemic control in intensive care unit: A randomized, open-label, clinical study

Abstract: Background:Intravenous insulin is the cornerstone in the management of hyperglycemia in the Intensive Care Unit (ICU). We studied the efficacy of liraglutide compared with insulin in the ICU.Materials and Methods:In this prospective, open-labeled, randomized study, we included 120 patients (15–65 years, either sex) admitted to ICU with capillary blood glucose (CBG) between 181 and 300 mg/dl. We excluded patients with secondary diabetes and APACHE score >24. The patients were divided into two groups (n = 60) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 15 A glucagon-like peptide-1 agonist has shown non-inferiority in glycemic control in intensive care unit (ICU) patients, most of which did not have preadmission diabetes, but an increase in nausea. 16 There are no specific studies on use of metformin, sodium-glucose cotransporter-2 inhibitors, pioglitazone, or acarbose in hospitalized patients, but experience shows that in selected patients they are safe to use. While in the past guidelines had recommended temporary interruption of metformin treatment before exposure to contrast media, most current guidelines recommend such interruption only in patients with chronic renal failure (with a cutoff of glomerular filtration rate of <60 or <45 mL/min per 1.73 m 2 ).…”
Section: Treatment With Non-insulin Antihyperglycemic Medicationsmentioning
confidence: 99%
“… 15 A glucagon-like peptide-1 agonist has shown non-inferiority in glycemic control in intensive care unit (ICU) patients, most of which did not have preadmission diabetes, but an increase in nausea. 16 There are no specific studies on use of metformin, sodium-glucose cotransporter-2 inhibitors, pioglitazone, or acarbose in hospitalized patients, but experience shows that in selected patients they are safe to use. While in the past guidelines had recommended temporary interruption of metformin treatment before exposure to contrast media, most current guidelines recommend such interruption only in patients with chronic renal failure (with a cutoff of glomerular filtration rate of <60 or <45 mL/min per 1.73 m 2 ).…”
Section: Treatment With Non-insulin Antihyperglycemic Medicationsmentioning
confidence: 99%
“…6 Another study of hyperglycemic patients with DM in the intensive care unit found that liraglutide had an impact comparable to that of intravenous insulin for glucose control, less hypoglycemia, and more gastrointestinal adverse effects as compared with insulin treatment. 7 We are aware of only one study with noncritically ill inpatients with DM. This study found that mean daily blood glucose improved without significant adverse effects with the GLP-1 receptor agonist called exenatide plus bolus insulin as compared with treatment with exenatide alone.…”
mentioning
confidence: 99%
“…One perioperative study of DM patients comparing liraglutide, insulin infusion, or subcutaneous insulin found that liraglutide was associated with the lowest glucose levels 6 . Another study of hyperglycemic patients with DM in the intensive care unit found that liraglutide had an impact comparable to that of intravenous insulin for glucose control, less hypoglycemia, and more gastrointestinal adverse effects as compared with insulin treatment 7 …”
mentioning
confidence: 99%